Riflessioni sulla ricerca di un metodo per la conoscenza e la cura della realtà mentale umana - Masillo, Alice; Fiori Nastro, Paolo (Il sogno della farfalla, 2007)
If we look at the history of medicine we realize that there has never been a real separation and autonomy between the science of psychiatry and the medicine of the body: mental illnesses have always been and are still considered organic illnesses of the brain. What follows is that most people afflicted with mental illnesses are considered incurable and are merely given a form of assistance including of a pharmaceutical type. One of the causes of this difficult research into mental illnesses and their dynamics can be put down to the lack of a study method (given that the mind and its thoughts constitute a reality which cannot be perceived by the five senses, in contrast to all the other organs of the body), which can see beyond the obvious realities of our waking lives, behaviour and articulate language. This study can only take place if we overcome two thoughts which are culturally deep-seated in common thinking. One is that human identity lies in reason and therefore a person who is mentally ill is someone who has lost his reason thus allowing the irrational to emerge, which coincides with the animality and the innate wickedness that lies within; the second is complementary to the first and it too derives from a religious thought that views everything in man which is not reason as spiritual soul, pertaining to the realm of faith and credence. In conclusion, the possibility of paving a way to knowledge and curing mental illnesses emerges once we have overcome these never before questioned dogmas and embark on a method of research that has as its principle focus the non-conscious or irrational reality present in each one of us, linked to but autonomous from our biological reality.